The effect of dynamic legal tradition on financial development: panel data evidence - Voghouei, Hatra; Mohamed, Azali; Law, Siong Hook (Springer, 2013)
This study examines the effect of dynamic legal tradition on financial development. In line with the theory of “dynamic legal tradition” proposed by Beck et al. (Law, politics, and finance. World Bank, Washington, DC, 2001), political variables are employed in the analysis to assess whether these variables could affect the legal environment and hence financial development in countries with different adaptability. The empirical results from the panel data of 60 counties for the period 1980–2006, show that political power could change the legal environment, especially in common law countries, which in turn could affect the development of financial systems. The result demonstrates that political factors that promote shareholder rights greatly influence the development of financial system followed by political factors that promote investor protection.